(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Our proposition is that certain “details” (catalysis, according to Barthes) reveal the presence of disciplinary power in the sphere of modern fiction. Our analysis starts with some of the descriptive units of Purén Indómito, which we consider to be a direct precedent for this revelation, and we conclude with the novella, Martín Rivas, and the short story, El matadero. The text dating from the colonial period gives a detailed account of daily life in the kingdom of Chile, describing the strategies of the sovereign power, while the modern stories highlight the presence of disciplinary power. Thus, the purpose of the dramatic details recounted in Purén is to ensure the legal-moral intervention of the monarch in the kingdom. In realist works, on the other hand, these details show the actions of organisations to subject and discipline the people, just as it occurs in Martín Rivas and El matadero. In this case, the narrative strategy is to exhibit the details of the foul, barbarous, reactionary customs of Latin American societies in order to discipline and purify them, and thus transform them into modern, productive nations.